Moderating Effect of Earnings Management on the Relationship Between Corporate Social Responsibility Disclosure and Profitability of Banks in Indonesia - Suteja, Jaja; Gunardi, Ardi; Mirawati, Annisa (International Journal of Economics and Financial Issues, 2016)
This study aims to obtain empirical evidence of earnings management as a moderating variable between corporate social responsibility (CSR) and profitability. This research was conducted by taking a sample of banking companies listed in the Indonesia Stock Exchange in 2010–2014. Data were collected using purposive sampling. The statistical method used was moderated regression analysis. Findings proved that CSR disclosure positively and significantly influences a company's profitability. By contrast, eaarnings management had a negative and significant influence as the moderating variable on the relationship between CSR and a company's profitability. These results suggested that a high level of earnings management, which leads to an enhanced CSR program, corresponds to weak profitability of the banking companies. Keywords: corporate social responsibility, earnings management, profitability, banking sector, Indonesia JEL Classifications: G2, M14